Segmentierte Ausbildungsmärkte Berufliche Chancen von Hauptschülerinnen und Hauptschülern im Wandel - Protsch, Paula (Verlag Barbara Budrich, 2014)
Why have the training opportunities for students of the German Hauptschule - the secondary school with the lowest level of graduation possible in Germany - changed since the 1950s? The author does not focus the explanation on young people, to whom deficits are often ascribed. Instead, she examines the role of employers in the segmentation of the training market and the increasing restriction of career opportunities.